Descriptive analysis and earthquake prediction using boxplot interpretation of soil radon time series data. (December 2019) - Tareen, Aleem Dad Khan; Nadeem, Malik Sajjad Ahmed; Kearfott, Kimberlee Jane; Abbas, Kamran; Khawaja, Muhammad Asim; Rafique, Muhammad
Abstract: Correlation of radon anomalies with meteorological parameters and earthquake occurrence has been reported in many studies. This paper reports descriptive statistical analysis and boxplot contingent earthquake prediction based upon soil radon time series data. Data has been collected over a fault line, passing beneath the Muzaffarabad, for the period of one year. Soil radon gas (SRG) was measured using RTM 1688-2 radiometric instrument (made by SARAD GmbH). The range of radon in soil was found to be 14349 Bqm −3, whereas the ranges of temperature, pressure and relative humidity were found as 38.50 C 0, 29 mbar and 67% respectively. SRG data shows that time series follows normal distribution. Values of coefficient of variation (CV) indicate the consistency of the recorded values of radon in soil and metrological parameters. Variance inflation factor (VIF) and Durbin Watson test (d) indicate a moderate multicollinearity and autocorrelation between variables. The analysis of radon time series using boxplots and meteorological parameters show specific patterns in radon concentrations (outliers, variant IQRs, first quartile values, and median values) due to pre-earthquake underground seismic activities. On the basis of these patterns earthquake may be more early predicted without using complicated predictive systems. Boxplots also predicted that there is no significant pattern found in dispersion of meteorological factors measured in this study. To the best of our knowledge this is first ever attempt to predict earthquake using boxplot explanation. Graphical abstract: Time series trend of 222 Rn and meteorological parameters. Image 1 Highlights: Correlation of radon anomalies with meteorological parameters and earthquake occurrence is investigated. Coefficient of variation indicate the consistency of the recorded values of radon in soil. Boxplots show specific patterns in radon concentrations due to pre-earthquake seismic activities. Study reveals the importance of monitoring soil radon in order to investigate the possible earthquake prediction.